Outcome Evaluation of a Pilot Study Using “Nudges” - Dave, Jayna M.; Chen, Tzu-An; Oceguera, Amanda M.; Cullen, Karen W.; Thompson, Deborah I. (International Journal of Child Health and Nutrition, 2015)
Background: Every school day, over 31 million U.S. children eat school lunches. Unfortunately, students often do not choose the healthy options in the school cafeteria. This paper describes outcome results of a pilot study using “nudges” to improve elementary school students’ fruits and vegetables selections. Methods: A pilot study was conducted from January to May 2012, in six intervention schools and 2 control schools. A behavioral economics-based intervention was conducted using “nudges” or cues from the cafeteria (staff encouragement to select fruit and vegetables, food labels, “Harvest of the Month” posters), school (morning announcement messages, prompts regarding cafeteria food selections), and parents (school newsletter articles, parent listserve messages) to promote students’ selection of fruits and vegetables in the school cafeteria. The serving data from the point-of-service machine provided fruits and vegetables served per student per day. Results: There were no significant differences in the number of servings of fruits and vegetables served per student per day, averaged over the study period. Process data revealed low implementation of the intervention components, which may partially explain results. Conclusions: Low implementation of nudges led to non-significant results in this pilot study. However, providing environmental cues are important and warrant further research with full implementation. Starting 2012, the new meal pattern includes two vegetables and a fruit serving for lunch; and two fruit servings for breakfast. Minimal cost interventions should be explored to facilitate successful implementation of new school meal guidelines.